Effect of Early Childhood Malnutrition on Tooth Eruption in Pakistan Adolescents - Ubaid Ullah, Huma Tahir, Mohammad Munib, Zarak Khan, Muhammad Tahir, Muhammad Amique Ur Rehman (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Child malnutrition has long-term consequences. Malnourished children are less productive physically, cognitively, and emotionally they are more prone to chronic diseases and impairments than healthy children. The present study aimed to assess the effect of early childhood malnutrition on tooth eruption in Pakistan adolescents. Materials and Methods: This cross-sectional study was carried out on 226 adolescents in the Department of Dentistry, Tertiary Care Hospital, Rawalpindi from January 2020 to June 2020. A structured questionnaire was used for administration of all adolescents. Each adolescent underwent dental caries and status of eruption was assessed and recorded. Weight for age, weight for height, and height for age were three different indices calculated in anthropometric data. Nutritional status of adolescents was calculated. Data analysis was done using SPSS version 27. Results: Of the total 226 adolescents, the prevalence of moderate/severe wasting of muscles, stunted, and underweight were 15% (n=34), 61.9% (n=140), and 48.7% (n=110) respectively. Out of 34 wasting adolescents, the frequency of moderate and severely wasted weight for height (wasting) was 9% (n=20) and 6% (n=14) respectively. Among 140 stunned adolescents, the incidence of moderate and severe stunned adolescents were 23.5% (n=53) and 38.5% (n=87) respectively. Of the 110 underweight adolescents, the incidence of moderately underweight and severely underweight were 32% (n=72) and 16.7% (n=38) respectively. A considerably greater proportion of individuals with wasting had a pattern of delayed eruption compared to those without wasting. There were 27.3% of patients who had delayed eruption alongside a decayed tooth. Conclusion: The present study revealed that besides delaying tooth eruption in adolescents and affecting oral health, malnutrition increases childhood caries. Throughout adolescence age, there was a correlation between eruption patterns or tooth exfoliation and both nutritional deficiency (stunting). Keywords: Tooth eruption, Malnutrition, Wasting, Under nutrition, Underweight.